Analisis Faktor-Faktor yang Mempengaruhi Permintaan Untuk Berlangganan Internet - Muhammad Azhari; Dyfan Yolanda Lazuardi Subekti (Forum Kerjasama Pendidikan Tinggi (FKPT), 2023)
The Internet is a rapidly expanding technology sector that is highly competitive and fosters significant innovation. It serves as a universal medium for participation and boasts the deepest penetration in human history. The advent of the Internet and digital technology has significantly enhanced individuals' abilities to perform daily tasks, conduct research, communicate with individuals outside their immediate environment, and make discoveries. This research aims to identify the variables that impact the demand for internet services within the urban area of Bandung. The variables under investigation encompass internet pricing, mean household earnings, educational attainment of the household head, family size, and age of the household head. The present study employs data from the websites of Indihome, Biznet, First Media, and the Central Statistics Agency (BPS) spanning 2006 to 2021. The method employed for data analysis in this study was the Ordinary Least Square (OLS) approach. Based on the t-test results, it is known that the t-count value is 7.063 and the significance value is 0.000, while the age variable produces a t-count value of 7.309 and a significance value of 0.000. According to the findings, there exists a correlation between the number of household occupants and the age of the household head, with the level of internet usage in Bandung City. As individuals age, their inclination to subscribe to internet services increases, leading internet providers to prioritise their marketing efforts towards the productive age group. A positive correlation exists between the number of individuals in a household and the level of demand for internet subscriptions. As such, internet service providers may benefit from marketing to households with larger family sizes. The number of individuals residing in a household can significantly influence the demand for Internet services.